Palladium/Copper‐Catalyzed Oxidative CH Alkenylation/N‐Dealkylative Carbonylation of Tertiary Anilines1. Issue 40 (14th August 2013) - Shi, Renyi; Lu, Lijun; Zhang, Hua; Chen, Borui; Sha, Yuchen; Liu, Chao; Lei, Aiwen
<x xml:space="preserve">Abstract</x> CH/CN activation: The first palladium/copper‐catalyzed aerobic oxidative CH alkenylation/N‐dealkylative carbonylation of tertiary anilines has been developed. Various functional groups were tolerated and acrylic ester could also be suitable substrates. This transformation provided efficient and straightforward synthesis of biologically active 3‐methyleneindolin‐2‐one derivatives from cheap and simple substrates.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>